The impacts of climate change on water resources of Lebanon-Eastern Mediterranean - Mohamad R. Khawlie (Fondazione Eni Enrico Mattei (FEEM), 2001)
Contrary to current notions about water abundance in Lebanon, the country is facing serious problems of unavailability, both in quantity and quality, geographical and sectoral. Even though this is due to several existing human-related aspects, i.e. management, ill-finance, non-integration and lack of relevant awareness on water use, the new dimension of climate change is unfortunately adding to the water problems in the country.Databases in Lebanon are not quite consistent and accurate, implying difficulty in interpreting correctly trends of change. Water supplies vary in the country from typically mild wet Mediterranean at the coast (600-800m.m.), through oromediterranean at the mountains (800-1200m.m.), to semi-arid inland (200 + 400m.m.). But actual records on the supply, i.e. precipitation, reflect a decreasing pattern over the last century. This is in agreement with predicted trends of temperature and precipitation values obtained from the GCM models over Lebanon. The HadCM2/HHGGax model predicts an average of 1.6°C increase in temperature by the year 2020, and an equivalent average of about 3% less precipitation. Water balance is overall still positive, but deficits are commonly felt locally. The projection in ten to fifteen years, however, predicts an annual deficit of up to 800m.c.m. with the business as usual.The expected resultant impacts of climate change on resources, natural settings and human settings are directly related to water. The former includes, in addition to water itself, forestry, biodiversity and fisheries. In the latter two are incorporated inland and coastal zones as well as all the productive sectors. Cross impact structural analysis can reveal which socio-economic variables are most influenced, and then a driving power/dependency chart can reveal four types of strong or weak drivers, or otherwise. In view of the above, adaptation measures are given at strategic, population and individual levels with different opportunities from short to medium to long-term phases.
Keywords: Q2; Q24; 330; Climate change; water; vulnerability; socio-economic adaptations; Klimawandel; Wasser; Wasserversorgung; Libanon